Sepiolite-Embedded Binary Nanocomposites of (Alkyl)Methacrylate-Based Responsive Polymers: Role of Silanol Groups of Fibrillar Nanoclay on Functional and Thermomechanical Properties - BEŞLİ, NUR SENA ÖKTEN; Orakdogen, Nermin (Elsevier, 2021)
Binary nanocomposites filled with fibrillar nanoclay sepiolite (SP) was manufactured using a hydrophilic terpolymer matrix containing 2-(diethylamino)ethyl methacrylate, hydroxyethyl methacrylate and 2-acrylamido-2-methyl-1-propanesulfonic acid. A direct correlation between dispersion of nanofillers, matrix-filler local interaction and improvement of macroscopical mechanical properties was obtained. Mechanical testing revealed that incorporation of SP nanofillers impart to terpolymer matrix a higher degree of reinforcement. Besides fibrous structure of SP, the interactions between silanol (-SiOH) groups present along fibers and terpolymer chains are responsible of extent of reinforcement of nanocomposites. The increase in modulus imparted by incorporation of -SiOH groups reflected a continuous increase in crosslinking density created by terpolymer-nanofiller interactions. Effective crosslink density of nanocomposites was expressed by a cubic polynomial function of SP loading. Swelling ratio of SP nanofiller containing nanocomposites was found to highly decrease at CSP > 3.50%(w/v), with regard to clay-free terpolymers reflecting strong interactions between pendant hydroxyl, carbonly, tertiary amino groups of terpolymer matrix and silanol groups of SP. Excellent pHresponsive swelling was observed in the range of pH 2.1?10.7 and the nanocomposites swelled in acidic conditions depending on the amount of protonated diethyl amino groups. Sensitivity sequence of terpolymer nanocomposites to mono- and di-valent cations with a common anion (Cl-) on swelling was Na+ > K+ > Mg2+. The control of quantity of SP fibers and polymerization temperature allows to manage mechanical properties by just tuning chemical architecture of terpolymer/clay nanocomposites. SP reinforcement of terpolymers can enrich various further characteristics such as targeted delivery of biomolecules or drugs.
Keywords: Nanocomposite Cryogel; Sepiolite; Fibrous Clay; Mechanical Properties; Elasticity